2020
DOI: 10.1590/1980-5373-mr-2019-0582
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution and Mechanical Properties of As-Cast Mg-12Zn Alloys with Different Al Additions

Abstract: In this study, Mg-12Zn magnesium alloys alloyed with Al additions (0, 2, 4, 6, 8 and 10, wt.%) were fabricated by permanent mould casting. The Al content on their microstructure and mechanical properties were systematically examined with an optical microscope (OM), a scanning electron microscope (SEM), an X-ray diffractometer (XRD) and mechanical tests at room temperature. The experimental results indicate that the microstructure of the alloys is mainly composed of α-Mg and semi-continuous or continuous eutect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The phases are evidenced in much darker features and lamellar type structure, as magnified in the inset figure. The morphology of eutectic or intermetallic phases of Mg17Al12 gradually evolved from a random distribution to network or continuous phases with the increase of Al addition [29].…”
Section: Methodsmentioning
confidence: 99%
“…The phases are evidenced in much darker features and lamellar type structure, as magnified in the inset figure. The morphology of eutectic or intermetallic phases of Mg17Al12 gradually evolved from a random distribution to network or continuous phases with the increase of Al addition [29].…”
Section: Methodsmentioning
confidence: 99%
“…This, in turn, reduces the stress/strain accumulation that initiates cracking. In terms of the effects of RE on the precipitation strengthening, it was reported that intermetallics can refine the grain size of the α-Mg matrix [14,15], resulting in the change of fracture mode from cleavage to ductile. Furthermore, the segregation [16,17] and precipitation [18] of RE atoms reduce the grain boundary mobility, changing the dynamic and static recrystallization textures.…”
Section: Introductionmentioning
confidence: 99%